2021
DOI: 10.3390/en14092549
|View full text |Cite
|
Sign up to set email alerts
|

Linear Induction Motors in Transportation Systems

Abstract: This paper provides an overview of the Linear Transportation System (LTS) and focuses on the application of a Linear Induction Motor (LIM) as a major constituent of LTS propulsion. Due to their physical characteristics, linear induction motors introduce many physical phenomena and design constraints that do not occur in the application of the rotary motor equivalent. The efficiency of the LIM is lower than that of the equivalent rotary machine, but, when the motors are compared as integrated constituents of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…All these problems were also discussed in this Special Issue of Energies. Similar research about design, simulation and electrical machine optimization are also discussed in some previous publications [19][20][21][22] not included in this Special Issue.…”
mentioning
confidence: 69%
“…All these problems were also discussed in this Special Issue of Energies. Similar research about design, simulation and electrical machine optimization are also discussed in some previous publications [19][20][21][22] not included in this Special Issue.…”
mentioning
confidence: 69%
“…It has also been observed that most high-power applications of electric motors, such as high-performance cars (e.g., Tesla and Porsche) employ fluid-cooled electric motors It has also been observed that most high-power applications of electric motors, such as high-performance cars (e.g., Tesla and Porsche) employ fluid-cooled electric motors for better cooling efficiency compared to fan cooling, which also takes up space and can lead to overheating. Electric motors are used for various applications ranging from industrial to domestic applications, and induction motors (rotating or linear) are the most used units [7][8][9][10][11]. Water-cooling systems might suffer from leakage issues if not properly designed and maintained.…”
Section: Introductionmentioning
confidence: 99%
“…Factors affected to ATP include income, transportation needs, total transportation costs, travel intensity, total expenditure per month, type of activity, and percentage of income for transportation needs. Willingness To Pay (WTP) is the willingness of users to pay for the services they receive [12]- [15]. Factors that affected the WTP include the production of transportation services by entrepreneurs, the quality and quantity of services provided by entrepreneurs, user benefits for transportation, and user income.…”
Section: Introductionmentioning
confidence: 99%